Big Web data, small focus: An ethnosemiotic approach to culturally themed selective Web archiving. Issue 2 (23rd July 2015) - Huc-Hepher, Saskia
This paper proposes a multimodal ethnosemiotic conceptual framework for culturally themed selective Web archiving, taking as a practical example the curation of the London French Special Collection (LFSC) in the UK Web Archive. Its focus on a particular 'community' is presented as advantageous in overcoming the sheer scale of data available on the Web; yet, it is argued that these ethnographic boundaries may be flawed if they do not map onto the collective self-perception of the London French. The approach establishes several theoretical meeting points between Pierre Bourdieu's ethnography and Gunther Kress's multimodal social semiotics, notably, the foregrounding of practice and the meaning-making potentialities of the everyday; the implications of language and categorisation; the interplay between (curating/researcher) subject and (curated/research) object; evolving notions of agency, authorship and audience; together with social engagement, and the archive as dynamic process and product. The curation rationale proposed stems from Bourdieu's three-stage field analysis model, which places a strong emphasis on habitus, considered to be most accurately (re)presented through blogs, yet necessitates its contextualisation within the broader (diasporic) field(s), through institutional websites, for example, whilst advocating a reflexive awareness of the researcher/curator's (subjective) role. This, alongside the Kressian acknowledgement of the inherent multimodality of on-line resources, lends itself convincingly to selection and valuation strategies, whilst the discussion of language, genre, authorship and audience is relevant to the potential cataloguing of Web objects. By conceptualising the culturally themed selective Web-archiving process within the ethnosemiotic framework constructed, concrete recommendations emerge regarding curation, classification and crowd-sourcing.